1967
DOI: 10.1111/j.1467-6494.1967.tb01435.x
|View full text |Cite
|
Sign up to set email alerts
|

Own height, sex, and liking in the judgment of the heights of others1

Abstract: For a long time it has been known that a person's own characteristics often infiuence his judgments about the same or related characteristics m other people The defense mechanism of projection can be viewed as one form of this phenomenon, as when a stmgy person judges other people around him to be stmgy (Sears, 1936). A less obvious form of this general phenomenon occurs when the characteristic m question is not a personahty trait but rather is a physical charactenstic which hes on an "objective" physical cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
2

Year Published

1978
1978
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 10 publications
1
17
2
Order By: Relevance
“…Kassarjian (1963), for instance, found that people's voting intentions correlated with the perceived height of presidents: prior to the 1960 election between Kennedy and Nixon, 68.1% of those who planned to vote for Kennedy believed Kennedy to be taller, whereas only 47.3% of those who planned to vote for Nixon thought Kennedy was taller (Kennedy was actually slightly taller than Nixon). Similarly, Ward (1967) found that self-reported liking for President Lyndon B. Johnson was significantly correlated with his estimated height. Another striking example is reported by Singleton (1978): after Nixon fell from grace and was forced to leave office, people estimated that his successor, Jimmy Carter, was taller than the disgraced former president.…”
Section: Introductionmentioning
confidence: 92%
“…Kassarjian (1963), for instance, found that people's voting intentions correlated with the perceived height of presidents: prior to the 1960 election between Kennedy and Nixon, 68.1% of those who planned to vote for Kennedy believed Kennedy to be taller, whereas only 47.3% of those who planned to vote for Nixon thought Kennedy was taller (Kennedy was actually slightly taller than Nixon). Similarly, Ward (1967) found that self-reported liking for President Lyndon B. Johnson was significantly correlated with his estimated height. Another striking example is reported by Singleton (1978): after Nixon fell from grace and was forced to leave office, people estimated that his successor, Jimmy Carter, was taller than the disgraced former president.…”
Section: Introductionmentioning
confidence: 92%
“…By contrast, general overestimates of a target quantity are less commonly reported. For example, although judgments of average height are correlated with own height, the mean of these judgments shows no bias (Ward 1967).…”
Section: Projection/false Consensusmentioning
confidence: 99%
“…The authors also demonstrated an own‐anchor effect in females' weight estimates of male targets, but this effect was weaker than in males' estimates. Based on these findings, Flin and Shepherd (see also MacLeod et al., 1994; Ward, 1967) argued that the own‐anchor effect is stronger for same‐gender height and weight estimates.…”
mentioning
confidence: 98%
“…Although the dominant picture from the own‐anchor/projection literature is that assimilation is most prevalent in same‐gender estimates (e.g., Robbins & Krueger, 2005), a couple of studies have also reported assimilation in women's cross‐gender estimates (Flin & Shepherd, 1986; Ward, 1967). Why is this the case?…”
mentioning
confidence: 99%